2019
DOI: 10.1155/2019/3802613
|View full text |Cite
|
Sign up to set email alerts
|

Case of Inherited Partial AZFa Deletion without Impact on Male Fertility

Abstract: Male factor infertility accounts for 40–50% of all infertility cases. Deletions of one or more AZF region parts in chromosome Y are one of the most common genetic causes of male infertility. Usually full or partial AZF deletions, including genes involved in spermatogenesis, are associated with spermatogenic failure. Here we report a case of a Caucasian man with partial AZFa region deletion from a couple with secondary infertility. Partial AZFa deletion, involving part of USP9Y gene appears to be benign, as we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…However, the testicular tissue of this patient revealed pre-meiotic and meiotic germ cells in most seminiferous tubules with small numbers of post-meiotic spermatids, consistent with spermatogenic arrest but not SCO. More recently, USP9Y was clearly excluded as an essential spermatogenesis gene because inherited deletions limited to USP9Y were identified in fertile men 17,18 , and, accordingly, USP9Y is now thought to act preferentially as a fine-tuner of germ cell maturation 19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the testicular tissue of this patient revealed pre-meiotic and meiotic germ cells in most seminiferous tubules with small numbers of post-meiotic spermatids, consistent with spermatogenic arrest but not SCO. More recently, USP9Y was clearly excluded as an essential spermatogenesis gene because inherited deletions limited to USP9Y were identified in fertile men 17,18 , and, accordingly, USP9Y is now thought to act preferentially as a fine-tuner of germ cell maturation 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The relevance of each of these genes for spermatogenesis is under debate for decades 16 . USP9Y, encoding a ubiquitously expressed ubiquitin C-terminal hydrolase, has been excluded as a singular disease gene for spermatogenic failure because genomic variants, including complete gene deletions, were found to be paternally inherited [17][18][19] . UTY encodes a histone demethylase whose expression is not limited to testicular tissue and was only recently described to be expressed in human type A spermatogonia located at the basal membrane of seminiferous tubules 20 .…”
mentioning
confidence: 99%
“…Alksere et al . 44 described a Caucasian man who was infertile despite having a partial deletion of USP9Y (sY84 and sY1323) and normal sperm; his father was likewise affected by the deletion. It has been suggested that partial AZFa deletions may not always result in azoospermia and that USP9Y may not play a decisive role in spermatogenesis.…”
Section: Vertical Transmission Of Azf Microdeletionsmentioning
confidence: 99%
“…Owing to the high proportion of segmental duplications, the Y chromosome exhibits the most significant CNVs of all human chromosomes (Liu et al., 2021). Over the last decade, Y‐chromosome microdeletions have been extensively reported (Alksere et al., 2019; Araujo et al., 2020). These microdeletions are clustered in a hotspot region known as the azoospermia factor (AZF), which can be divided into three nonoverlapping subregions (AZFa, AZFb and AZFc) (Kamiński et al., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the high proportion of segmental duplications, the Y chromosome exhibits the most significant CNVs of all human chromosomes (Liu et al, 2021). Over the last decade, Y-chromosome microdeletions have been extensively reported (Alksere et al, 2019;Araujo et al, 2020). These microdeletions are clustered in a…”
mentioning
confidence: 99%